The process of burnout among professional sport coaches through the lens of self-determination theory: a qualitative approach - Bentzen, M.; Lemyre, P.-N.; Kenttä, G. (Sports Coaching Review, 2014)
Using a qualitative retrospective approach, this paper investigates how some work-related demands led to burnout among four professional coaches. Self-determination theory (SDT) offered a sound theoretical framework to better understand the motivational process leading to serious negative outcomes (Ryan & Deci, 2002). Findings indicated that all coaches experienced working in a maladaptive environment, exemplified by experiencing very heavy workloads, a lack of leader support, and work-related conflicts. These experiences had a detrimental effect on the coaches' motivation. Psychological need thwarting and a shift towards a more controlled form of motivation explained why coaches became increasingly at risk for burning out, a process that evolved over time. All four coaches experienced a wide range of burnout symptoms. Findings from this study highlight the importance for sports organizations to better cater for the psychological needs of professional coaches to prevent burnout.